Data reduction for the representation of curves by piecewise polynomials - Maas, Christoph; Levermann, Frank (Zielona Góra: Uniwersytet Zielonogórski)
In the course of the development of an industrial CAD-software package a method had to be developed for storing curves given by a scanner in bitmap format. The objective is to reduce the amount of data necessary for defining the curve while allowing a certain deviation of the stored curve from the original one. Two solutions are presented based upon Hermite-interpolation or B-Spline-interpolation of the bitmap, respectively. The solutions involve questions about an appropriate parametrization of the data and about easy editing of the results by the user of the program.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka